Parents' Perspectives of Cleft Lip and/or Palate Services: A Qualitative Interview. (May 2013) - Nelson, Pauline A.; Kirk, Susan A.
The study aimed to explore in depth the perspectives of parents about their child's cleft services. Purposive and theoretical sampling produced a diverse sample of mothers and fathers with children aged 20 weeks to 21 years. Parents were recruited from a specialist cleft center in the U.K. Qualitative, in-depth, face-to-face interviews were carried out with 35 parents. Interviews were audio-recorded, transcribed, and analyzed using grounded theory to identify salient data categories. Findings revealed that parents' positive views about services rested on their perceptions of cleft-care practitioners as competent and trustworthy, possessing highly developed communication skills and the ability to provide continuity of care to families. At the same time, some mothers and fathers identified unmet support needs relating to information delivery and content as well as the coordination of services across the treatment course. More individualized information about treatment was desired; in particular, some parents had incomplete information about their child's surgical procedures, associated risks, and postsurgical recovery. Parents wanted better coordination of services with regard to communication about surgical cancellations, a child's transition to adult services, and having a key professional to link with throughout their child's treatment course. Routine assessments to gauge parents' needs could be built into cleft-care pathways so that more individualized information and support might be delivered to families in more consistent ways over long-term treatment.